Case report: Identification of a frameshift mutation in GC enrichment and the GCC repeat region of the androgen insensitivity receptor (AR) gene in a patient with complete androgen insensitivity syndrome by whole-exome sequencing (WES) combined with specific PCR and deep sequencing - He, Xiaojing; Ma, Qingya; Zhang, Qiaoli; Hong, Xutao; Qi, Ming; Li, Yongkai; Li, Xiaodong (Frontiers in Genetics, 2022)
Background: Androgen insensitivity syndrome (AIS) is an X-linked recessive hereditary disease caused due to a reduced or absent function of the androgen receptor (AR) protein encoded by the AR gene (OMIM-Gene# 313,700). Genetic testing is important in the diagnosis, clinical management, and prevention of AIS (MIM# 300,068). The AR (HGNC: 644) pathogenic variant detection rate ranges from 65% to 95% for patients with complete AIS (CAIS) and 40%–45% for patients with partial androgen insensitivity syndrome (PAIS). Identification of a pathogenic mutation in the AR confirms the diagnosis of AIS, especially in the milder forms that may have a phenotypic overlap with other disorders of sex development. Improvement of the molecular diagnostic rate of AIS is urgently required in clinical practice. We reported the results of the molecular diagnosis of a patient with CAIS who failed previously in either the traditional Sanger sequencing or next-generation sequencing (NGS). Using whole-exome sequencing (WES) combined with a special polymerase chain reaction (PCR) and deep sequencing, we successfully identified a pathogenic variant, a hemizygous mutation (c.1395-1396insGA), in the GC-enriched and unstable GCC repeat regions of the AR gene of the proband. Conclusion: The results may be advantageous for the improvement of the detection rate of AIS, as well as other inherited disorders whose disease-causing genes contain GC-enriched and unstable GCC repeat regions.